ショウワキチ シュウヘン ノ ビリョウ ゲンソ ノ ブンプ (II) ラングホブデ チイキ ノ タイセキブツ チュウ ノ ビリョウ キンゾク ブンプ - 三島, 昌夫; ミシマ, マサオ; 山県, 登; ヤマガタ, ノボル; Mishima, Masao; Yamagata, Noboru (国立極地研究所, 1977)
P(論文) 堆積物と水中に含有される重金属(銅,鉄,マグネシウム,マンガン,亜鉛)濃度を,湿式分解を使用し,フレームおよびフレームレス原子吸光によって測定した.試料はラングホブデ地区より採取した.その結果,特に雪鳥沢の堆積物中の濃度分布は,ほぼ対数正規分布を示した. Trace metals (Cu, Fe, Mg, Mn and Zn) concentration distribution in water and sediment were determined by atomic absorption methods with flame and flameless systems using wet dissolution method. The samples were collected from Langhovde, Antarctica. The result showed an approximate log-normal distribution of concentration of metals in sediment of the Yukidori Valley. departmental bulletin paper